Process-oriented writing and text quality in L3 German – cognitive challenges and motivational aspects - Fredriksson, Christine; Rosén, Christina (Linguistik Online, 2026)
Abstract This article presents the results from an intervention study on process-oriented writing in L3 German among 21 Swedish students in an upper secondary school. Our study investigates the relationship between process-oriented writing and text quality concerning accuracy, content, text length, and syntactic complexity. We also consider how individual variables, such as cognitive load (CL), learner engagement, and achievement goals, relate to the learning outcome in process-oriented writing. Our data consist of students’ mind maps, student texts, and questionnaires. Regarding accuracy, results show a slight improvement in basic morphology and syntax. As for text quality, there is a correlation between a well-prepared mind map and a text rich in content, whereas only a weak relationship between mind map and text length was found. In contrast to previous studies (cf. Pon/Varga 2017), our analysis shows only a weak relationship between text length and syntactic complexity. Concerning cognitive load and engagement, the students experienced problems when giving and receiving feedback. Even so, most students perceived the work with process-oriented writing as engaging. Overall, they express a clear desire to develop their writing and appreciate the opportunity for planning and time for reflection.